PENDIRIAN RUMAH IBADAT MENURUT PERATURAN BERSAMA MENTERI AGAMA DAN MENTERI DALAM NEGERI NO. 8 DAN 9 TAHUN 2006 TENTANG PENDIRIAN RUMAH IBADAT (Studi Kasus Kota Pekanbaru) - Ismardi Ismardi (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2011)
Writing works through to hit pluaralisme's problem at Indonesian, notably deep religion area have evoked a lot rf conflict at various region, particularly sectioned East lndonesian area. That conflict really confiscate energy and side exhaustive thinking because no has touched to pine politics, social and economic, as one of Poso's happening. Government has done various effort to muffle conflict among people gets religion, as do dialogue among beragama.'s people. Expected by society can unlimber to do discussion with other religion people that variably view about life fact That dialogue by it self will enrich knowledge both of party in order to dance equation who can make life base on good terms in society